Mood Lamp Berbasis Microcontroller - Arief Budijanto; Tamaji (FT- UNDAR, 2018)
— Mood lamp is a lamp made from RGB (red, green, blue) led that can be programmed based on its color through remote control, so that the color of the lamp can be determined by the user according to his mood. This lamp is designed using 89C2051 microcontroller with low power technology and uses RGB leds that can be programmed into several colors via a remote control. The remote control signal in this study uses the standard NEC remote code. The results of the led lights experiment can be programmed into 7 colors, namely red, blue, cyan, yellow, magenta, white, and green. The purpose of the results of this study in the future so that it can be used as a business opportunity in the field of creative industries, because this mood lamp can be used as a garden light, home porch lights, restaurants and cafes.